ISRÃâÃLIYYÃT DAN BIAS GENDER DALAM PENAFSIRAN AL-QURâAN - Norhidayat, Norhidayat (Jurnal Ilmu Ushuluddin, 2012)
This paper tries to explore about the Israilliyyat and gender bias in interpretating theAlquran. This paper emphasizes that the infiltration the Isra âÃ®liyyÃ¢t narrations intafseer books were not necessarily lead to the interpretation of al-Qurâ an in thosebooks were related to the gender bias. This conclusion denied the Muslim feministinterpretation that in the classic books there are some gender-biased interpretation whichare caused by infiltration of IsraâÃ®liyyÃ¢t narrations. Special studies of Isra âÃ®liyyÃ¢t andconcept of women ceation in al-Tabari interpretation strengthens the conclusions of thispaper and also denied the allegations of Muslim feminists popularized.